A Regional Smoothing Block Sparse Bayesian Learning Method With Temporal Correlation for Channel Selection in P300 Speller - Zhao, Xueqing; Jin, Jing; Xu, Ren; Li, Shurui; Sun, Hao; Wang, Xingyu; Cichocki, Andrzej (Frontiers in Human Neuroscience, 2022)
The P300-based brain-computer interfaces (BCIs) enable participants to communicate by decoding the electroencephalography (EEG) signal. Different regions of the brain correspond to various mental activities. Therefore, removing weak task-relevant and noisy channels through channel selection is necessary when decoding a specific type of activity from EEG. It can improve the recognition accuracy and reduce the training time of subsequent models. This study proposes a novel block sparse Bayesian-based channel selection method for the P300 speller. In this method, we introduce block sparse Bayesian learning (BSBL) into the channel selection of P300 BCI for the first time and propose a regional smoothing block sparse Bayesian learning (RSBSBL) by combining the spatial distribution properties of EEG. The RSBSBL can determine the number of channels adaptively. To ensure practicality, we design an automatic selection iteration strategy model to reduce the time cost caused by the inverse operation of the large-size matrix. We verified the proposed method on two public P300 datasets and our collected datasets. The experimental results show that the proposed method can remove inferior channels and work with the classifier to obtain high classification accuracy. Hence, RSBSBL has tremendous potential for channel selection in P300 tasks.